STUDY OF THE PATTERNS OF HEALTH FINANCE UTILIZATION IN THE NATIONAL HEALTH SECURITY (JKN) ERA OF NON-PBI PARTICIPANTS AT H. ABDUL MANAP HOSPITAL - Yulia Frischa; Dwi Noerjoedianto; Hubaybah Hubaybah (Pusat Riset dan Inovasi Nasional, 2023)
The National Health Insurance is a mechanism designed to protect individuals and families in providing health services to their citizens, especially the poor, in order to reduce financial barriers to obtaining health services. It is known that Non-PBI Mandiri participants who have been late paying premiums for at least six months show that 70.5% of respondents register as BPJS participants on the grounds that they need health financing guarantees in the near future, either on their own or according to directions from doctors or paramedics. Therefore, the aim of this research is to look at the pattern of health financing utilization in the era of National Health Insurance (JKN) for non-PBI participants at H.Abdul Manap Hospital. This study uses a qualitative research method with a phenomenological approach. Data were obtained from 9 informants by conducting in-depth interviews at H.Abdul Manap Hospital with qualitative data analysis. The results of this study (1) Psychological factors found a pattern of moral hazard phenomena with a tiered referral system, because there was a tendency to use BPJS membership benefits only to finance expensive or high-cost health services identified in research informants, (2) Personal factors found an alleatory pattern , because they feel they have benefited from the sustainability of the program and there are differences in understanding from the demand side.